"Why can't they be in the community?" A policy and practice analysis of transforming care for offenders with intellectual disability. Issue 3 (5th May 2015) - Alexander, Regi; Devapriam, John; Michael, Dasari; McCarthy, Jane; Chester, Verity; Rai, Rahul; Naseem, Aezad; Roy, Ashok
Abstract : Purpose: – The purpose of this paper is to describe key policy and practice issues regarding a significant subgroup of people with intellectual disability – those with offending behaviour being treated in forensic hospitals. Design/methodology/approach: – The reasons why psychiatrists continue to be involved in the treatment of people with intellectual disability and mental health or behavioural problems and the factors that may lead to patients needing hospital admission are examined. Using two illustrative examples, three key questions – containment vs treatment, hospital care vs conditional discharge and hospital treatment vs using deprivation of liberty safeguards usage in the community are explored. Findings: – Patients with intellectual disability, mental health problems and offending behaviours who are treated within forensic inpatient units tend to have long lengths of stay. The key variable that mediates this length of stay is the risk that they pose to themselves or others. Clinicians work within the framework of mental health law and have to be mindful that pragmatic solutions to hasten discharge into the community may not fall within the law. Originality/value: – This paper makes practical suggestions for the future on how to best integrate hospital and community care for people with intellectual disability, mental health and offending behaviours.